Uptake of genetic testing for germline BRCA1/2 pathogenic variants in a predominantly Hispanic population - McGuinness, Julia E. (Cancer Genet, 2019)
BACKGROUND: Genetic counseling is under-utilized in women who meet family history criteria for BRCA1 and BRCA2 (BRCA1/2) testing, particularly among racial/ethnic minorities. We evaluated the uptake of BRCA1/2 genetic testing among women presenting for screening mammography in a predominantly Hispanic, low-income population of Washington Heights in New York City. METHODS: We administered the Six-Point Scale (SPS) to women presenting for screening mammography at Columbia University Irving Medical Center (CUIMC) in the Washington Heights neighborhood of New York, NY. The SPS is a family history screener to determine eligibility for BRCA1/2 genetic testing based upon U.S. Preventive Services Task Force (USPSTF) guidelines that has been validated in low-income, multiethnic populations. RESULTS: Among women who underwent screening mammography at CUIMC between November 2014 and June 2016, 3,055 completed the SPS family history screener. Participants were predominantly Hispanic (76.7%), and 12% met family history criteria for BRCA1/2 testing, of whom <5% had previously undergone testing. CONCLUSIONS: In a multiethnic population, a significant proportion met family history criteria for BRCA1/2 testing, but uptake of genetic testing was low. Such underutilization of BRCA1/2 genetic testing among minorities further underscores the need to develop programs to engage high-risk women from underrepresented populations in genetic testing services.